The art of molecular dynamics simulation - Rapaport, D. C. (Cambridge University Press, 2004)
The extremely powerful technique of molecular dynamics simulation involves solving the classical many-body problem in contexts relevant to the study of matter at the atomistic level. The second edition of the book includes a substantial amount of new material as well as completely rewritten software.